2007
DOI: 10.1371/journal.pone.0001361
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Association (GWA) Study for Early Onset Extreme Obesity Supports the Role of Fat Mass and Obesity Associated Gene (FTO) Variants

Abstract: BackgroundObesity is a major health problem. Although heritability is substantial, genetic mechanisms predisposing to obesity are not very well understood. We have performed a genome wide association study (GWA) for early onset (extreme) obesity.Methodology/Principal Findingsa) GWA (Genome-Wide Human SNP Array 5.0 comprising 440,794 single nucleotide polymorphisms) for early onset extreme obesity based on 487 extremely obese young German individuals and 442 healthy lean German controls; b) confirmatory analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
395
5
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 455 publications
(439 citation statements)
references
References 21 publications
27
395
5
8
Order By: Relevance
“…[1][2][3][4] The role of FTO variants as predisposing to obesity in Caucasian populations is now established more firmly. [5][6][7][8] The association to general fatness irrespective of its distribution is confirmed throughout the range of fatness 9 and the association between FTO variants and obesity is also seen in Japanese people. 10 In search for the mechanism by which allelic variation in FTO affect adiposity, both central 11 and peripheral 12,13 mechanisms have been examined.…”
Section: Introductionmentioning
confidence: 76%
“…[1][2][3][4] The role of FTO variants as predisposing to obesity in Caucasian populations is now established more firmly. [5][6][7][8] The association to general fatness irrespective of its distribution is confirmed throughout the range of fatness 9 and the association between FTO variants and obesity is also seen in Japanese people. 10 In search for the mechanism by which allelic variation in FTO affect adiposity, both central 11 and peripheral 12,13 mechanisms have been examined.…”
Section: Introductionmentioning
confidence: 76%
“…People carrying variants in the FTO gene are more susceptible to obesity. Many other groups have subsequently confirmed such a correlation among individuals of different cohorts (Hinney et al, 2007;Ohashi et al, 2007;Scuteri et al, 2007). FTO locates on chromosome 16 in human and on chromosome 8 in mouse.…”
Section: Fto and Obesitymentioning
confidence: 81%
“…The common FTO gene variant (rs9939609) was subsequently used in a population-based GWAS to identify this gene as the first to be associated with common childhood obesity (Frayling et al 2007). Consistent with this result, a later case-control GWAS performed with lean and extremely obese German children indicated that this particular FTO gene variant was associated with common childhood obesity (Hinney et al 2007). A number of other studies performed with both children and adults indicated that this FTO gene variant was associated with increased and preferential consumption of energy-dense macronutrients, particularly foods enriched with saturated fatty acids (Cecil et al 2008;Timpson et al 2008;Bauer et al 2009).…”
Section: Obesity Susceptibility Genes That Interact With Dietary Fatsmentioning
confidence: 82%
“…Five of these obesity susceptibility genes (FTO, MC4R, MAF, NPC1, and PTER) were identified in the first or second casecontrol GWAS for early-onset (less than 6 years of age) and morbid-adult obesity (BMI C 40 kg/m 2 ) (Hinney et al 2007;Meyre et al 2009). More recent meta-analysis of several case-control GWAS using *40,000 individuals has determined that three of these obesity susceptibility genes (FTO, MC4R, and NPC1) are also associated with body fat percentage which serves as an accurate measure for whole body adiposity (Kilpelainen et al 2011;den Hoed et al 2012).…”
Section: Gene-diet Interactions Predisposing To Common Childhood Obesitymentioning
confidence: 99%